Implementasi Proses Asuhan Gizi Terstandar pada Pasien Diabetes Melitus dengan Berbagai Komorbiditas: Study Kasus - Betty Yosephin Simanjuntak; Lydia Fanny; Derie Erawan; Titi Enyliana (Universitas Sultan Ageng Tirtayasa, 2026)
Diabetes mellitus is a metabolic disorder characterized by chronic and sustained elevations in blood glucose levels. Type 2 diabetes mellitus is the most common type and is often accompanied by complications such as hypertension, anemia, and urinary tract infections. This study aims to assess the results of implementing a standardized nutritional care process in patients with type 2 diabetes mellitus with complications of hypertension, anemia, and urinary tract infections. This study used an observational design with a case study approach in an inpatient (Tn H, 56 years) at Harapan Doa Hospital in Bengkulu City for three days of observation. The nutritional care process included assessment, diagnosis, intervention, and monitoring and evaluation. Data collected included dietary intake, anthropometry, biochemistry, and the patient's clinical physical condition. The results showed a gradual increase in energy and protein intake during the intervention, as well as a decrease in random blood sugar levels from 363 mg/dL to 157 mg/dL. In addition, there was an improvement in clinical condition, characterized by stabilization of vital signs and a decrease in blood pressure to near normal. Thus, the implementation of standardized nutritional care through a diabetes mellitus diet and the DASH dietary approach is effective in helping improve the patient's metabolic and clinical conditions.